New rules of social media shopping: Personality differences of U.S. Gen Z versus Gen X market mavens. Issue 4 (6th November 2020) - Goldring, Deborah; Azab, Carol
Abstract: This study compares differences in market mavenism between two generations: the young adult portion of Gen Z, born from approximately 1997 through 2012, to their Gen X parents, born from 1965 through 1980, using a field study of traits, shopping habits, and social media behaviors. Building on generational cohort theory, we conducted paired comparisons across generations and in mavens versus non‐mavens. We found differences between mavens and non‐mavens related to value consciousness, marketplace interfaces, status consumption, need for uniqueness, and social outcomes decision making. Significant differences were also found between GenZs and GenXs mavens when it comes to status consumption and social outcomes decision making. We also analyzed social media engagement by product category and platform and finally, suggest managerial implications.